Primary health care professionals’ knowledge about compulsory notification diseases and health problems - Oliveira, Raiane Melo de; Oliveira, Andressa Suelly Saturnino de; Frota, Natasha Marques; Felipe, Gilvan Ferreira (Revista de Enfermagem da UFPI, 2024)
Objective: To evaluate Primary Health Care professionals’ knowledge about compulsory notification diseases and health problems. Methods: A cross-sectional study conducted between August and December 2021 with 30 Primary Health Care professionals from Tauá - Ceará. A questionnaire was used for the sociodemographic and professional characterization and for the knowledge assessment of compulsory notification diseases and health problems. The data were analyzed with descriptive and inferential statistics. Results: Of the 30 participants, six (20.0%) correctly identified all items with compulsory notification diseases and health problems. The following was properly identified by almost all participants: dengue (27; 90.0%); leprosy (26; 86.7%); and tuberculosis (26; 86.7%). Severe work-related accidents (17; 56.7%), domestic violence (17; 56.7%) and schistosomiasis (17; 56.7%) obtained the lowest proportions of correct identification. The professionals that had greater knowledge about compulsory notification concepts and guidelines were also those who were able to properly identify more diseases and health problems (rs=0.475; p=0.008). Conclusion: The professionals have difficulty identifying compulsory notification diseases and health problems, especially those with little prevalence in the municipality where they work and problems such as domestic violence and severe work-related accidents. Investing in the permanent education of professionals can contribute to reducing underreporting.